Pengaruh pemberian tepung biji nangka sebagai bahan pengisi terhadap kualitas bakso daging itik petelur afkir - Feri Fariadin; Permata Ika Hidayati; Dyah Lestari Yulianti (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2018)
This research to know the effect of the use of jackfruit seed flour as a filler material to the quality of laying duck meatballs. The material used in this study were jackfruit flour 0% (P0), 5% (P1), 10% (P2), 15% (P3) and 20% (P4) This method uses Group Random Design (RAL) with four repetitions. Using single variance analysis data. The results of the organoleptic test and cooking shrinking showed that in the treatment of P0 and P1 with the seed starch level of 0-5% jackfruit there was a very real effect (P <0.01). While on P2, P3 and P4 do not influence good elasticity, aroma, taste, color, and texture. This is why the more the addition of starch level will decrease. Suggested in the process of making meatballs duck meat using 95% tapioca starch with 5% starch seed jackfruit